Rural development in Taiwan : some lessons - Tomar, J.S. (New Delhi, 1990)
Fifteen years ago, Taiwan was as poor as many other countries in Asia. Today, it claims to possess foreign reserves of US $75 billion, the world's third highest, with per capita income of its citizens exceeding US $5,000. Its economic miracle has made the island nation one of the richest in the world and world's 13th biggest trading nation. It is second ranking export country in Asia. Since the 1950s, Taiwan has had virtually no strikes or lockouts yet its industrial labour is perhaps highest paid in Asia. An average skilled construction labourer in Taiwan earns about US $ 34 a day and a girl at the toll tax barrier gets a monthly wage of about US $ 400. A junior school teacher's salary is more than what an Army General earns in many other countries. An average family nowadays maintains a car and atleast one two-wheeler. In the rural areas, more than 95% families own refrigera tors, electric cookers, electric fans, gas stoves and more than 70% families own colour televisions and telephones. On the food front, the daily per capita calorie intake exceeds 2,950, the highest in Asia. Taiwan imports wheat, not for human consumption, but to feed cattle. Taiwan's economic success and resulting prosperity did not come overnight-it took about 30 years of organised planning to reach the present level. The political leadership of the country has also contributed substantially towards economic reconstruction of Taiwan. For instance, the Minister of Economic Affairs is an economics graduate and the President is a Ph D in agricultural economics. The ratio between people in the top 20 per cent and those in the bottom 20 per cent of earnings was only 4.1 to 1, one of the lowest in the world. This book makes an attempt to narrate the strategies applied by Taiwan in the sphere of rural development to attain a great degree of success in such a short period.
Keywords: Rural development Taiwan